Alliteration and rhyme in English advertising slogans as persuasive stylistic devices - Karimova , Dilshoda Ulug’bek qizi; Satibaldiyeva , Nigora Alimqul qizi (The Lingua Spectrum, 2026)
This article examines the role of phonetic stylistic devices, particularly rhyme and alliteration, in English advertising slogans as tools of persuasion. The aim of the study is to analyse how these sound-based strategies improve audience engagement, emotional appeal, and memorability. A qualitative methodology is employed, based on the analysis of widely recognized advertising slogans from global brands. The research involves identifying phonetic devices, classifying them, interpreting their stylistic functions, and assessing their persuasive effect. The findings demonstrate that rhyme and alliteration significantly contribute to the development of memorable and rhythmic slogans which affect customer perception on a subconscious level. Additionally, the study highlights how repetition of initial sounds and end sounds reinforces brand recall, creates musicality, strengthens linguistic patterns, attracts consumer attention, builds emotional resonance, and supports the strategic construction of persuasive and impactful advertising messages in competitive markets. The study concludes that phonetic stylistic devices are essential in modern advertising discourse and suggests further research on other sound techniques in digital contexts.